2023
DOI: 10.3390/ma16216848
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Development of Industrial Solid Waste in Tunnel Grouting Materials: Feasibility, Performance, and Prospects

Bolin Jiang,
Mengjun Wu,
Shanshan Wu
et al.

Abstract: With rapid infrastructure development worldwide, the generation of industrial solid waste (ISW) has substantially increased, causing resource wastage and environmental pollution. Meanwhile, tunnel engineering requires large quantities of grouting material for ground treatment and consolidation. Using ISW as a component in tunnel grouts provides a sustainable solution to both issues. This paper presented a comprehensive review of the recent advancements in tunnel grouting materials using ISW, focusing on their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 132 publications
(156 reference statements)
0
2
0
Order By: Relevance
“…Liu et al explored the influence of material design parameters on the physical and mechanical properties of recycled asphalt to determine the optimal processing parameters using response surface methodology [4]. Jiang et al presented a comprehensive review of the recent advancements in tunnel grouting materials using industrial solid waste [5]. Xu et al used controlled low-strength materials for backfilling narrow spaces to achieve efficient and high-quality backfilling effects for pipeline trenches [6].…”
Section: Highlights In the Present Issuementioning
confidence: 99%
“…Liu et al explored the influence of material design parameters on the physical and mechanical properties of recycled asphalt to determine the optimal processing parameters using response surface methodology [4]. Jiang et al presented a comprehensive review of the recent advancements in tunnel grouting materials using industrial solid waste [5]. Xu et al used controlled low-strength materials for backfilling narrow spaces to achieve efficient and high-quality backfilling effects for pipeline trenches [6].…”
Section: Highlights In the Present Issuementioning
confidence: 99%
“…Utilizing industrial solid wastes (ISWs) in grouting can help reduce the usage of conventional grouting materials like cement and provide an economic and environment-friendly solution for waste management. Several studies explored the feasibility of utilizing various industrial solid wastes, such as fly ash, waste clay brick powder (WCBP), and different types of slag such as ground granulated blast furnace slag (GGBS), fuming furnace slag (FFS), and crushed fuming furnace slag (CFFS), as a partial replacement for cement in grouting applications [104][105][106][107][108][109][110][111]. Overall, the recent studies demonstrated that slags can partially replace up to 50% of cement in grouting applications [104].…”
Section: Use Of Industrial Solid Wastes In Groutingmentioning
confidence: 99%